New management requirements in an accelerating changing external environment - A. D. Mezhevov; A. V. Zheltenkov; S. A. Ryabichenko (Вестник университета)
The article examines the impact of scientific and technological progress and changes in politics and economics on management in organisation. The effectiveness of contemporary governance systems can be assessed using well-known criteria: average gain; a cautious observer (Wald’s criterion); Laplace criterion; maximax et al. The use of the VUCA-world philosophy has predetermined the search for a solution to the problem of developing new requirements for the knowledge and skills of managers and specialists in the organisation, the availability and formation of competences. In line with the aim of the work – to find new approaches and requirements for management decision-making and organisation management – new requirements for assessing the changing environment, the business response to these changes, and new aspects of managerial and personnel behaviour in organisations have been identified. It has been revealed that in business training it is necessary to pay more attention to the formation of the desire for self-improvement and the development of the ability to overcome difficult situations, to divide goals into subgoals, tasks into stages. The methods of analysis and synthesis, induction and deduction have been used. Applying the results of the study in practice will improve the management of contemporary organisations.